To solve the equation \( 2(x + 8) = 2x + 8 \), we will go through the following steps:
Step 1: Distribute the 2 on the left side.
\[ 2(x + 8) = 2 \cdot x + 2 \cdot 8 \]
This simplifies to:
\[ 2x + 16 = 2x + 8 \]
Reasoning: This step uses the Distributive Property, which states that \( a(b + c) = ab + ac \).
Step 2: Subtract \( 2x \) from both sides.
\[ 2x + 16 - 2x = 2x + 8 - 2x \]
This simplifies to:
\[ 16 = 8 \]
Reasoning: This step uses the Subtraction Property of Equality, which states that if you subtract the same value from both sides of an equation, the equality is still maintained.
After performing these steps, we find that the resulting statement \( 16 = 8 \) is not true.
Thus, for this equation there are no solutions (it is inconsistent) since the simplified form leads to a false statement.